Implementasi Fungsi Organisasi Melalui Kegiatan Pemberdayaan Masyarakat Dalam Pemanfaatan Sumber Daya Alam Untuk Meningkatkan Kesehatan Lingkungan Di Desa Sumber Sari Kecamatan Kabawetan Kabupaten Kepahiang - Erpina, Popi; Sari , Lola Anma; Amanda, Dea Susita; Pebriani, Emi; Darmawansyah, Darmawansyah; Azissah, Danur (Utami Publisher, 2025)
The Implementation of organizational functions through community empowerment activities in the utilization of natural resources to improve environmental health in Sumber Sari Village, Kabawetan District, Kepahiang Regency, is a program aimed at increasing residents' awareness in sorting waste in an easy and structured way. Waste segregation is important to reduce the volume of waste that pollutes the environment and facilitate the recycling process. According to research conducted by Pratiwi (2020), sorting organic and non-organic waste can help reduce negative impacts on the environment and provide benefits in more efficient waste management. Through this program, residents are invited to actively participate in maintaining the cleanliness of their environment, starting from sorting waste at home to disposing of it in the bins provided. Objective: To increase community awareness and participation in wise and sustainable waste management to create a clean, healthy, and environmentally friendly environment. Methods: This community service was carried out in Sumber Sari Kebawetan village. The subjects of the service are mothers who are members of the Sumber Sari Village group with a total of 20 participants This service activity is the distribution of organic and non-organic waste boxes with the Head of Sumber Sari Village. Results and Discussion: From the results of observations after the installation of garbage cans, there was a change in the habits of the community